The orthodontic mini-implant clinical handbook - Cousley, Richard R. J. (Hoboken, NJ : Wiley-Blackwell, 2020)
'Offers the very latest on the theory and practice of integrating mini-implant techniques into clinical practice This all-new second edition of The Orthodontic Mini-implant Clinical Handbook provides a thoroughly revised and expanded update to the theoretical and practical aspects of using mini-implants in orthodontic practice. Taking a practical step-by-step approach with hundreds of clinical images, it presents updated clinical techniques and new clinical cases, covering all topics of importance for utilising mini-implants. It also includes a new chapter on mini-implant anchored maxillary expansion appliances. It begins with a chapter that looks at mini-implant principles and potential complications, before moving onto clinical and design factors for maximising mini-implant success. Other chapters cover incisor retraction; molar distalisation and protraction; intrusion and anterior openbite treatments; bone anchored rapid maxillary expansion; orthognathic surgical uses; and ectopic teeth. Provides a comprehensive guide to both theoretical and practical advice for the use of mini-implants in orthodontic practice Covers updated clinical techniques and new clinical cases Presents a new chapter on mini-implant anchored maxillary expansion appliances Takes a highly illustrated step-by-step approach ideal for clinical practice The Orthodontic Mini-Implant Clinical Handbook is an essential resource to orthodontists, maxillofacial surgeons, practicing dentists, and anyone with an interest in mini-implant skeletal anchorage. The new edition would offer a significant expansion and update to this guide to practical and theoretical aspects of mini-implants in dental practice. The new edition would grow by about 90 pages and 200 clinical photographs, with updated clinical techniques, more recent clinical cases, and new information and references throughout. A new chapter will present information on mini-implant anchored maxillary expansion appliances, and the information on miscellaneous orthodontic uses will newly appear as a standalone chapter. The Second Edition will retain the step-by-step, highly illustrated approach of the first edition. Clinical tips are included throughout, making this an ideal patient-side resource'--
Orthodontic mini-implant principles and potential complications -- Maximising mini-implant success : patient (anatomical) factors -- Maximising mini-implant success : design factors -- Maximising mini-implant success : clinical factors -- Mini-implant planning -- Mini-implant insertion -- Retraction of anterior teeth -- Molar distalisation -- Molar protraction -- Intrusion and anterior openbite treatments -- Transverse and asymmetry corrections -- Ectopic teeth anchorage -- Bone-anchored maxillary expansion -- Orthognathic surgical uses.
Includes bibliographical references and index.
Keywords: Orthodontic Anchorage Procedures; Dental Implantation; Dental Implants; Miniaturization